2018
DOI: 10.22271/ortho.2018.v4.i1b.16
|View full text |Cite
|
Sign up to set email alerts
|

Management of idiopathic clubfoot by Ponseti’s technique

Abstract: Background and objective: Idiopathic Congenital Talipes Equinovarus (CTEV) is a complex deformity that is difficult to correct. The treatment of clubfoot is controversial and continues to be one of the biggest challenges in paediatric orthopaedics. Most orthopaedicians agree that the initial treatment should be non-surgical and should be started soon after birth. We aimed to study a short term follow up Children included in the study were assessed for the severity of the deformity using the Pirani severity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…This systematic review included nine studies that met the inclusion criteria [14][15][16][17][18][19][20][21][22] (Table 1). Two studies did not report the study design [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review included nine studies that met the inclusion criteria [14][15][16][17][18][19][20][21][22] (Table 1). Two studies did not report the study design [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review included nine studies that met the inclusion criteria [14][15][16][17][18][19][20][21][22] (Table 1). Two studies did not report the study design [21,22]. While most of the studies were prospective [15,16,17,18], one was descriptive-retrospective [14], one was retrospective [19], and one employed a cross-sectional design [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were supported by [3] they studied the treatment of congenital clubfoot and found that 45% of infants their age were four months and the mean aged was 1.62 ± 0.898 months. As well as, [14] . They concluded that 64.86% of infants in six months and less than six months of follow-up to Ponseti's technique had excellent results.…”
Section: Discussionmentioning
confidence: 95%
“…Dewasa ini umumnya bedah ortopedi sepakat bahwa terapi inisial untuk CTEV harus dimulai dengan metode non-operatif sejak hari pertama kehidupan agar deformitas dapat dengan mudah dikoreksi re-alignment, mendapatkan hasil fungsional yang baik, dan mencegah terjadinya relaps. 4 Mengingat bahwa defek ini memiliki keterlibatan genetik dan memerlukan penanganan sedini mungkin maka penulis tertarik untuk menelusuri lebih lanjut baik dari aspek pencegahan yang dapat dikaitkan pada marriage counseling, maupun persiapan orang tua sejak masa prenatal, penanganan dini, dan rekonstruksi operatif lanjut agar dapat menjamin quality of life (QoL) yang layak.…”
Section: Pendahuluanunclassified